Comparison of expression for IL-15 and IL-18 on dendritic cells and macrophages upon infection with recombinant fowlpox virus versus wild type fowlpox virus - Yusof, Sakinah (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2015)
Fowlpox is a viral disease of chicken caused by fowlpox virus (FWPV). Compared to other viral infectious diseases, studies on the interaction of antigen-presenting cells (APC) such as dendritic cells (DCs) and macrophage with FWPV remains limited. Therefore, this work was aimed to characterize cytokine responses upon infection of recombinant fowlpox viruses (rFWPV) expressing H5 gene of avian influenza virus (AIV) compared to wild type FWPV on chicken DCs and macrophage cells. Chicken bone marrow cells were first isolated. The cells were differentiated into DCs (GM-CSF and IL-4 acted as supplements in RPMI media), or into macrophages (no supplements added). In order to quantify chicken IL-15 and IL-18 cytokine expression, qPCR assays based on real-time analysis were performed. Data suggested that rFWPV induced higher expression for IL-15 and IL-18 on macrophage while wild type FWPV induced higher expression for IL-15 and IL-18 on DC.